Identification of the multi-drug resistant genes in the bacteria isolated from the saliva of smoker oral cancer patients and comparative analysis with smoker normal individuals - Hasan, Samir; Siddique, Naisa; Alisa, Airina Jahan (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2023.